SEASONAL SPACE USAGE BY THE INTRODUCED PHARAOHS ANT, MONOMORIUM-PHARAONIS (L) (HYM, FORMICIDAE), IN INSTITUTIONAL SETTINGS IN BRAZIL AND ITS RELATION TO OTHER STRUCTURAL ANT SPECIES - Fowler, H. G.; Filho, F. A.; Bueno, O. C. (Blackwell Wissenschafts Verlag Gmbh, 1993)
In an institutional setting in Brazil, the pharaoh's ant, Monomorium pharaonis was found to be the dominant and most abundant ant present throughout the year. The only other regularly collected ant was the exotic Tapinoma melanocephalum. However, M. pharaonis dominated bait station visitations, although locally concentrated, with other species restricted to regions in which M. pharaonis was not found.